Standarisasi berat kalung emas hollow dengan metode PDCA di PT. X - Annabela Michaela Prasetyo; Jani Rahardjo (Jurnal Titra, 2015)
To control the production quality in terms of product weight, PT. X needs a standardization in production process. The weight standardization will help ease stocking process for both the company and the distributor. This research is used on the hollow product with chain type A with gold levels of 70%. Some of the products weight are not constant due to the variation of shrinkage percentage in every production process. The solution for this problem is to reduce the variation of shrinkage percentage levels in every production process using PDCA method. The improvement results obtained from PDCA method is shown on hammering, hollowing, and bombing process. On hammering process, a decrease in the shrinkage percentage variation is done by controlling the wire’s thick shrinkage percentage 15%-20% for a 5% shrinkage percentage. The percentage of necklace on hollowing process can’t be controlled, as a result an improvement is needed by giving an accurate range percentage standard, 49%-52% for chain A with gold levels of 70%. The weight shrinkage percentage in bombing process is depending on the size of small, medium, and large chain respectively 4%-5%, 5%-6%, 6%-7%.